Analisis Kekalahan Calon Petahana dalam Pemilihan Kepala Daerah di Kabupaten Flores Timur Tahun 2024: Studi terhadap Kekalahan Antonius Hubertus Gege Hadjon di Kecamatan Adonara Timur - Flaviana Lidia Yuyun; Rex Tiran; Ambrosius Dedi A. Sinu (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study is titled Analysis of the Incumbent's Defeat in the 2024 Regional Head Election in East Flores Regency (A Study of Antonius Hubertus Gege Hadjon's Defeat in East Adonara District), with the aim of analyzing the factors that led to the defeat of incumbent Antonius Hubertus Gege Hadjon in the 2024 Pilkada. This study uses Pierre Bourdieu’s political modality theory, including political, social, economic, and cultural capital. A qualitative approach with a descriptive method is employed, and data is collected through interviews with subjects consisting of the incumbent candidate, a religious leader, a youth leader, a community leader, two party representatives, and the success team. The study focuses on the support base in East Adonara District. The results of the study indicate that the incumbent's defeat was caused by the weakening of political capital, especially due to the vacancy in the regent’s position for two and a half years, which strengthened the opponent's position. This caused stagnation in public services and a decrease in the intensity of local government communication. In addition to these structural factors, weak internal party consolidation and public sentiment about uneven development also contributed to the defeat, indicating the incumbent's failure to manage his political capital amidst the dynamics of governance.